Induction of Immunological Tolerance by Oral Anti-CD3 - Andre Pires da Cunha; Howard L. Weiner (Clinical and Developmental Immunology)
In recent years, our knowledge about immunoregulation and autoimmunity has significantly advanced, but nontoxic and more effective treatments for different inflammatory and autoimmune diseases are still lacking. Oral tolerance is of unique immunologic importance because it is a continuous natural immunologic event driven by exogenous antigen and is an attractive approach for treatment of these conditions. Parenteral administration of anti-CD3 monoclonal antibody is an approved therapy for transplantation in humans and is effective in autoimmune diabetes. Orally administered anti-CD3 monoclonal antibody is biologically active in the gut and suppresses experimental models of autoimmune diseases. Orally delivered antibody does not have side effects including cytokine release syndromes, thus oral anti-CD3 antibody is clinically applicable for chronic therapy. Here we review findings that identify a novel and powerful immunologic approach that is widely applicable for the treatment of human autoimmune conditions.